Kritik Hamka Terhadap Praktik Pengultusan Makam Keramat Dalam Tafsir Al-Azhar - Muh. Awaluddin A Arifin; Achmad Abubakar; Muhsin Mahfudz (Dirosah Islamiyah, 2026)
This study will present Hamka’s critique of the practice of venerating graves in the Al-Azhar commentary, and then analyse this critique to examine Hamka’s position as a reformist using Hans Georg Gadamer’s theory of Historically Effected Consciousness. The aim of this study is to describe Hamka’s critique of the practice of venerating sacred graves in Al-Azhar’s exegesis and to analyse his historical influence as a reformist. This study employs a qualitative research method in the form of library research. The results of this study indicate that Hamka’s critique of the practice of venerating sacred graves can be divided into three categories: theological critique, epistemological critique, and sociological critique. Hamka’s criticism of the practice of venerating sacred tombs, when analysed through Hans Georg Gadamer’s theory of Historically Effected Consciousness, reflects Hamka’s.